TITIK KENDALI KRITIS (TKK) DAN DETEKSI KEHALALAN NUGGET IKAN “MJ”” KABUPATEN SEMARANG TAHUN 2016 - Trifany Arlita Prihandini; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Food safety and halal is a requirements that should be fulfilled by each foods that will distributed and consumed. HACCP (Hazard Analisys Critical Control Point) is a system that could be applied by food industries to producing a safety food and doesn’t contaminated by physical, chemical , and microbiological contamination. This system also used to determined a halal foods. The purposes of this research are to analyze critical control points and halal detection of MJ’s Fish Nugget in Semarang District. The sample of this research is fish nuggets and Top Manager as respondents. This research used kualitative and kuantitative methode. The kuantitative methode used to identified Escherichia coli, water contents, and pH of fish nuggets that tested in Balai Laboratorium Kesehatan Provinsi Semarang. The results of kuantitative research showed that 150µ/g of Escherichia coli are contained in tilapia, and below 3µ/g in fish nugget. Test of formalin showed a negative results both fish nugget or tilapia, 49,53% of water contents and pH 4,00. The kualitative methode used to describe a Top Manager’s commitments, analyze a critical control points, describe the equipments and environments, and determine a halal status of fish nuggets. The results of kualitative research showed that MJ Fish Nugget’s production have two critical control points there are steaming and storaged proccess, and two halal critical control points there are raw material handling and storaged proccess. This research concluded that the halal status of MJ’s Fish Nuggets is unclear, because they used a halal’s critical ingredient that not certified.